PENANAMAN NILAI-NILAI NASIONALISME DALAM PEMBELAJARAN SEJARAH PADA SISWA KELAS XI DI SMA NEGERI 5 PROVINSI MALUKU UTARA - Zulkifli, Zulkifli; Tomagola, Leny MS (Jurnal Pendidikan dan Ekonomi (JUPEK), 2024)
The aim of this research is to determine the role of teachers in instilling "Soekarano" nationalist values in class XI students in history learning at SMA Negeri 5 North Maluku Province. In the teaching and learning process teachers have an important role to increase learning motivation so that the teaching and learning process can be achieved well. For this reason, instilling nationalist values is very important so that students can know and interpret them and serve as a guide for students in formal, informal and non-formal education. To achieve this goal, history teachers have an important role in developing an understanding of the meaning of nationalism in the teaching and learning process. in history subjects in class XI students at SMA Negeri 5 North Maluku Province. Because history teachers do not just convey material that has been included in the history books provided, but this material provides motivation and encouragement to students so that learning objectives can be achieved well.